DETEKSI DINI OBESITAS SENTRAL PADA WANITA USIA SUBUR DI DESA JATI KALANG SIDOARJO - Aidha Rachmawati; Endah Mulyani; Diani Octaviyanti Handajani (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Jati Kalang Village is one of the villages in the Prambon Sidoarjo sub-district, where there are quite a several toddlers and women of childbearing age. Previously, the implementation of posyandu in Jati Kalang Village had rarely examined mothers; generally, the posyandu only screened the growth and nutritional status of children and the application of immunizations. The need for knowledge about central obesity in women of childbearing age is still lacking; most women or mothers underestimate it, even never checking the condition of central obesity they experience. The purpose of this community service activity is to map and report maternal health status by conducting early detection of health status related to central obesity. This activity attended by 78 wus or 78% of the 100 recorded with the results of 40 wus experiencing central obsession or about 51.28% and as many as 38 wus (48.72%) not obese.